Insights on the antiradical capacity and mechanism of phytocannabinoids: H-abstraction and electron transfer processes in physiological media and the influence of the acid-base equilibrium. (April 2023) - Boulebd, Houssem
Abstract: Phytocannabinoids are natural products primarily isolated from Cannabis sativa that exhibit the typical C21 terpenophenolic skeleton. This class of compounds has been shown to be effective in the treatment of various oxidation-related diseases, which has made their antioxidant properties the focus of increasing interest. In the present contribution, the primary antioxidant properties of eight representative phytocannabinoids have been systematically studied against a variety of biologically significant radical species using the density functional theory (DFT) method. The findings demonstrated that phytocannabinoids, in water at physiological pH, exhibit excellent radical scavenging capacity, mainly exerted by the single electron transfer (SET) process from the deprotonated state. In contrast, phytocannabinoids are moderate radical scavengers in non-polar environment via the formal hydrogen atom transfer (fHAT) process. Among the compounds examined, cannabichromene (CBC) and cannabifuran (CBF) had the greatest free radical scavenging capacity in water, surpassing even common antioxidants like BHT and Trolox. CBF is expected to have potent antiradical action toward peroxyl radicals, alkoxy radicals, and nitrogen dioxide in water at physiological pH. These results provide supporting evidence that phytocannabinoids may be useful in scavenging harmful free radicals in physiological environments. Graphical abstract: Image 1 Highlights: The radical scavenging capacity of eight phytocannabinoids was examined. The influence of polar and lipid physiological environments was considered. Phytocannabinoids behave like moderate-to-good radical scavengers in lipid media. Most phytocannabinoids are excellent radical scavengers in water at physiological pH. H-abstraction and electron transfer are the decisive processes in lipid and polar media, respectively. Cannabichromene and Cannabifuran are the most promising radical scavengers.